Tinjauan Prinsip Syariah Produk Uang Elektronik di Indonesia: Studi Kasus Pada Produk E-Money Bank Syariah Mandiri - Nurhasanah Nurhasanah; Agung Maulana; Aris Rusdiyanto (ITB AAS INDONESIA Surakarta, 2021)
The issue raised in this research is to discuss an evaluation of the sharia principles of electronic money (called E-Money) product owned by Bank Syariah Mandiri towards the operational mechanisms encompass transaction, flow, contract and managerial aspects of this product. This study aims to analyze E-Money product from a sharia perspective using the benchmark of fiqh muamalat which has been contained in the DSN-MUI fatwa, and related laws and regulations. The method used in this research is descriptive qualitative research. By using the method of content analysis and using interviews, involved observation, this research uses documentation study as the data collection technique. The conclusion from the writing of this thesis is that from a review of sharia principles, there are sharia problems in the aspect of the contract, this is because this product does not have a contract nomenclature in product operations that creates ambiguity (Gharar), as well as from the transaction aspect because the bank does not restrict or control goods which are sold by merchants in collaboration with banks, so it is feared that they can be used to buy non-halal goods.